STRATEGI KOMUNIKASI PUSTAKAWAN DAN PEMUSTAKA DALAM MENCARI SUMBER INFORMASI DI PERPUSTAKAAN - Armen Armen (UIN Imam Bonjol Padang, 2017)
From a religious perspective, we can easily answer that it is God who teaches us to communicate, using the intellect and language skills that are bestowed upon us. The Qur'an says,